Efficient Green Protocols for the Preparation of Pyrazolopyrimidines. Issue 23 (18th June 2021) - Kumar, Hansal; Das, Rudradip; Choithramani, Asmita; Gupta, Astha; Khude, Datta; Bothra, Gourav; Shard, Amit
Abstract: Pyrazolopyrimidine with all its isoforms occupy a noteworthy position in medicinal chemistry owing to their proven dominance in the modulation of a vast array of biological receptors, thereby mitigating numerous pathological conditions. The development of sustainable protocols, which integrate the principles of green chemistry in the synthesis process although challenging, offers the most appropriate way to conduct the sustainable synthesis of pyrazolopyrimidines. Due to the effectiveness of this nucleus and striking similarity to purines, they have been accessed using green as well as non‐green protocols. Analytical techniques like 2D NMR has been employed for the confirmation of pyrazolopyrimidines and their isomers besides the conventional single‐crystal X‐ray diffraction (XRD). Here, considering the rising awareness of sustainable protocols, we aimed at exploring this decade for green protocols for the synthesis of pyrazolopyrimidines and furnished products in excellent yields in this review. Protocols covered in this review include synthesis using green solvent, solvent‐free conditions, green catalyst, and catalyst‐free reactions. Also, synthesis of pyrazolopyrimidines assisted by microwave and ultrasound, as well as ionic liquid mediated synthesis are covered. It is estimated that this review shall throw some light upon the environmentally benign protocols to produce pyrazolopyrimidines which is itself a very important nucleus in the field of medicinal chemistry. Abstract : The review encloses the green synthetic protocols for preparing pyrazolopyrimidines‐ A scaffold offering diverse biological activities. It delivers elaborative explanation regarding the synthesis of all pyrazolopyrimidine isoforms, utilizing green reaction media, solvent‐free conditions, synthesis using microwave irradiation, ultrasound, catalyst‐free, and metal‐free approach providing significant yields. It covers several development methods for synthesis of pyrazolopyrimidines using ionic liquids as a reaction media. Moreover, it also provides the reported schemes and mechanisms offering deep and better understanding of the topic